Investigation of 37 years weather record and its relation to human health: A case study in Songkhla Province, Southern Thailand - Noppradit, P.; Pradit, S.; Muenhor, D.; Doungsuwan, N.; Whangsani, U.; Sama, N.; Towatana, P. (International Journal of Agricultural Technology, 2021)
The weather data from the Thai Meteorological Department during 1982-2018 were analysed and identified the climate change situation in Songkhla Province, Thailand. Result indicated that temperature, humidity, rainfall, sunlight and heat index was statistic significantly increased at p<0.05, while the monthly maximum wind speed decreased in temperature change which 33% less than global temperature change. The increase in temperature consequently affected the other parameters such as humidity, rainfall and heat index. Moreover, the storm frequencies in Songkhla were not increased. Their frequencies of occurrence were slightly fluctuated. Another finding was the storm arrival date slightly shifted to the end of year. The characterization of relationship between climate change and health conditions were related to the diseases e.g. gastroenteritis, dengue fever, malaria, blood infection disease and upper respiratory infection from the year 2002 to 2018. The secondary data of crucial meteorological factors were recorded. The results revealed that the morbidity rates per 1,000 population for gastroenteritis, blood infection diseases, upper respiratory infection that had positive statical relationship with the average annual relative humidity with r2 = 0.460, 0.461 and 0.486 ( p <0.05) respectively, whereas dengue fever and malaria are not related to statistical relationship with all the investigated climatic variables including the average annual rainfall. Probably climatic change would increase the outbreaks of the gastroenteritis, blood infection, upper respiratory diseases, while it had not affected on the spread of dengue fever and malaria according to topographic factor in the study area